CLIS Model Boosts Science Understanding in Indonesian Fifth Graders: Model CLIS Meningkatkan Pemahaman Sains pada Siswa Kelas 5 SD di Indonesia - Maghfiroh, Faiqotul; Setiyawati, Enik (Indonesian Journal of Education Methods Development, 2024)
This study investigates the impact of the Children Learning In Science (CLIS) model on fifth graders' science concept understanding. Using a quantitative one-group pretest-posttest design, 24 students from SDN Jeruk Purut 1 Gempol were tested with essay questions. The paired sample t-test showed a significant improvement (Sig. 0.00 < 0.05) in science understanding after applying the CLIS model. The N-Gain test indicated a medium-level improvement with a mean score of 0.6513. These results demonstrate that the CLIS model effectively enhances students' science comprehension, suggesting its broader potential for science education.Highlight: Significant impact of CLIS on science concept understanding. Medium category increase in science concept understanding. Valid and reliable instruments confirmed by expert judgment. Keywoard: CLIS, science education, fifth graders, quantitative study, conceptual understanding